2014
DOI: 10.1001/jamaoto.2014.979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Sucralfate vs Clindamycin on Posttonsillectomy Pain in Children Aged 6 to 12 Years

Abstract: Iranian Registry of Clinical Trials registration number: IRCT201303209014N16.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…As pain is a subjective symptom, the amount of analgesic used after tonsillectomy and the duration of analgesic use are accepted as objective criteria to evaluate pain. Pain after tonsillectomy lasts about 9 days, and the pain is at its most intense on post-operative day 1, and it decreases thereafter 12 . In our study, the average duration of analgesic use by patients was 3.53 ± 1.88 days.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…As pain is a subjective symptom, the amount of analgesic used after tonsillectomy and the duration of analgesic use are accepted as objective criteria to evaluate pain. Pain after tonsillectomy lasts about 9 days, and the pain is at its most intense on post-operative day 1, and it decreases thereafter 12 . In our study, the average duration of analgesic use by patients was 3.53 ± 1.88 days.…”
Section: Discussionmentioning
confidence: 45%
“…As the post-operative area is no longer covered by mucosa, there is an infection risk. Some studies have reported that antibiotics administered after tonsillectomy decrease pain by reducing local flora and inflammation 4 , 12 . Other studies have shown that antibiotic treatments have no effect on post-operative pain 5 , 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Karaman et al analyzed the effects of local antibiotic prophylaxis in tonsillectomy patients and found a reduction in both aerobic and non-aerobic bacterial counts in tonsillar niches compared with patients who had not received topical antibiotic therapy [20]. Local perioperative antibiotic prophylaxis remains an open issue, as some recent studies have confirmed reduced pain and postoperative bleeding in patients following local perioperative administration of clindamycin [37]. However, there is also research questioning this concept [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, the commonly prescribed acetaminophen may not be adequate for post-tonsillectomy pain relief without codeine and at higher doses it may cause hepatic toxicity (5). Therefore, there is an ongoing research on the investigation of effectiveness of many surgical and pharmacological products in post-tonsillectomy pain management (2,4,5,7,9,23,26). Subramayam et al (2) reported their own experience on the use of ATC acetaminophen, dexamethasone and ibuprofen in pain management as no increase in the incidence of inadequate pain control or serious complications.…”
Section: Discussionmentioning
confidence: 99%